The bulletin of the Metropolitan Museum of Art. (Metropolitan Museum of Art, 1905)
New ser. v. 6-29 include 77th-100th Annual report of the Trustees of the Metropolitan Museum of Art, 1946-1969-70 (previously and subsequently published separately).